A second species of the enigmatic whitefly genus Stenaleyrodes Takahashi (Sternorrhyncha, Aleyrodidae) - Martin, Jon H.; Streito, Jean-Claude (Zootaxa, 2003)
Stenaleyrodes papillote sp. nov. is described from coconut palms on Mayotte Island and in East Africa. It is only the second known member of this genus, whose systematic position has hitherto been uncertain. With use of both puparial and adult characters, the placement of Stenaleyrodes in the subfamily Aleurodicinae is supported, and the status of the subfamilies Aleurodicinae and Udamoselinae discussed.Stenaleyrodes papillote sp. nov. est décrite sur cocotier de l’Île de Mayotte et d’Afrique de l’Est. C’est seulement la deuxième espèce connue de ce genre, dont la position systématique demeure incertaine. Le statut des deux sous-familles Aleurodicinae and Udamoselinae est discuté. Malgré l’absence de pores composés et de griffes aux pattes du puparium, une observation attentive de S. vinsoni et des pupariums et adultes de la nouvelle espèce plaide pour le maintien du genre Stenaleyrodes dans la sous-famille des Aleurodicinae.